(untitled) (GEOmedia, 2024)
The head office of Kokudo Chiri-in, GSI for short, is in Tsukuba (Ibaraki Prefecture) a city located about an hour’s train ride northeast of Tokyo. The GSI could be said to be the National Agency for Geodesy and Cartography of Japan whose origins date back to the year 1869 (Meiji1), a period that is defined as the Meiji Restoration. The GSI, which is a Special Body of the Ministry for Land, Infrastructure, Transport and Tourism, had almost 700 employees in 2018 (Heisei 30). In Tsukuba the GSI manages a Science Museum of Map and Survey which I visited in 2019 (Reiwa 1).